anonymous
  • anonymous
precalc help please, giving medals and becoming fan!!! 1.) Find the first six terms of the sequence. a1 = -8, an = 5 • an-1 -8, -40, -200, -1000, -5000, -25,000 -8, -40, -35, -30, -25, -20 0, 5, -40, -35, -30, -25 -40, -200, -1000, -5000, -25,000, -125,000 2.)Find an equation for the nth term of the arithmetic sequence. -3, -5, -7, -9, ... an = -3 - 2 an = -3 + -2(n) an = -3 + -2(n + 1) an = -3 + -2(n - 1)
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
perl
  • perl
For the first one let's get you started. $$ \Large {a_1=-8 \\ a_2 = 5\cdot a_1= 5 \cdot (\text{-}8) }$$
hartnn
  • hartnn
similarly, to get a3, plug in n=3 in \(\Large a_n = 5 a_{n-1} \\ \Large a_3 = 5a_2 = ... ?\) and so on..
xapproachesinfinity
  • xapproachesinfinity
yu are still stuck?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

xapproachesinfinity
  • xapproachesinfinity
for the second one -3, -5, -7,- 9.... do you see that we are adding 2 each step
xapproachesinfinity
  • xapproachesinfinity
-2 i meant*
xapproachesinfinity
  • xapproachesinfinity
so a1=-3 a2=-3-2=-5 a3=-3-2-2=-7 a4=-3-2-2-2=-9 . . . . an=-3-2-2-2-2-2-2............-2 (-2 (n-1) times)=3-2(n-1)
xapproachesinfinity
  • xapproachesinfinity
correction an=-3-2(n-1)

Looking for something else?

Not the answer you are looking for? Search for more explanations.